2000
DOI: 10.3233/jad-2000-2104
|View full text |Cite
|
Sign up to set email alerts
|

The Thr183Ala Mutation, Not the Loss of the First Glycosylation Site, Alters the Physical Properties of the Prion Protein

Abstract: The abnormal form of the prion protein has increased resistance to protease digestion and is insoluble in non-ionic detergents. The normal prion protein is modified by the non-obligatory addition of two N-linked glycans. One pathogenic mutation, Thr to Ala at residue 183 of the human prion protein, blocks addition of the first glycan to the Asp residue 181. This mutation has been reported to result in intracellular retention of the mutant protein and its acquisition of pathogenic properties, presumably due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 14 publications
7
39
0
Order By: Relevance
“…Beyond this, our case supports the idea that the loss of Pro at residue 105 is sufficient to induce prion disease (which appears to favor GSStype pathology), and the specific amino acid substitution contributes to the PrP Sc conformation and ultimate phenotype. It is not clear why rPrP Sc-P105S lacks the diglycosylated fraction; however, our cell-based studies suggest that, in contrast to PrP T183A , 20,21 PrP P105S , like PrP V180I , is fully glycosylated and properly delivered to the plasma membrane. Thus, either the diglycosylated fraction of PrP P105S and PrP V180I is resistant to conversion, or the unglycosylated and monoglycosylated forms are selectively favored.…”
Section: Figure 3 Prp Amyloid In Prnp-p105smentioning
confidence: 69%
See 1 more Smart Citation
“…Beyond this, our case supports the idea that the loss of Pro at residue 105 is sufficient to induce prion disease (which appears to favor GSStype pathology), and the specific amino acid substitution contributes to the PrP Sc conformation and ultimate phenotype. It is not clear why rPrP Sc-P105S lacks the diglycosylated fraction; however, our cell-based studies suggest that, in contrast to PrP T183A , 20,21 PrP P105S , like PrP V180I , is fully glycosylated and properly delivered to the plasma membrane. Thus, either the diglycosylated fraction of PrP P105S and PrP V180I is resistant to conversion, or the unglycosylated and monoglycosylated forms are selectively favored.…”
Section: Figure 3 Prp Amyloid In Prnp-p105smentioning
confidence: 69%
“…The T183A mutation precludes glycosylation at position 181 and impairs trafficking of PrP to the plasma membrane, the normal cellular destination of PrP. 20,21 Although residue 105 is distant from the glycosylation sites at positions 181 and 196, an indirect effect on glycosylation might result from an effect on the normal cellular trafficking of PrP. To determine if the P105S mutation directly impairs PrP glycosylation, we expressed PrP carrying the P105S mutation in cultured HeLa cells and compared the glycosylation profile and plasma membrane localization with PrP carrying the T183A mutation.…”
Section: Figure 3 Prp Amyloid In Prnp-p105smentioning
confidence: 99%
“…This discrepancy of results obtained may be the result of a combination of factors: different point mutations introduced in the PrP gene, different constructs, distinct cell lines, random integration of the transgene, and different levels of Prnp expression or in some cases use of drugs to prevent glycosylation that can cause intracellular stress. Moreover, experiments that introduced the T182A mutation to abolish the attachment of sugars at the first site (16,20,21) may be misleading, since this mutated PrP can cause familial TSE disease (49,53) in a glycosylationindependent manner (54).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are somewhat contradictory to the reported failure of partially glycosylated PrP to be efficiently implanted in the cell surface (19,40,41), suggesting that the exact involvement of glycosylation for the migration of PrP to the surface and/or its stable localization at the membrane are yet to be fully understood. We note that Capellari et al (42) suggested in the past that glycan occupancy of the first PrP glycosylation does not appear to be essential for its transport through the secretory pathway.…”
Section: Discussionmentioning
confidence: 57%